Simplified design and CFD analysis of Francis turbine components for low-head micro-hydropower applications - Makhashya, Ujwal; Gurung, Kishor; Manandhar, Sunil; Adhikari, Neeraj (Kathmandu University Journal of Science Engineering and Technology, 2025)
This paper presents a simplified design methodology for Francis turbine components for the low-head micro-hydropower applications. The run ner is developed using the Bovet method, while the remaining components are designed taking the runner as the reference. For the design of a free vortex-type of spiral casing with circular cross-section, the guidelines provided by UNIDO are considered. Likewise, the guide vanes are modeled using the NACA airfoil profile, and the draft tube adopts a Bend-Spacer-diffuser arrangement to enhance pressure recovery. CFD simu lations are performed in ANSYS FLUENT to analyze flow characteristics, pressure distributions, and performance metrics across the distributor, runner, and draft tube. The distributor shows favorable pressure and velocity distributions with a minor head loss of 0.46 m. The runner pro duces a power output of 17.11 KW with a hydraulic efficiency of 92%, though it operated in off-design conditions, while the draft tube achieves effective pressure recovery despite a major head loss of 1.26 m. The turbine attains an overall efficiency of 83.5%, highlighting the feasibility of a simplified and cost-effective design for small-scale hydropower systems.